2021
DOI: 10.4103/jfmpc.jfmpc_2550_20
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of rheumatic fever and rheumatic heart disease among the population in taif, Saudi Arabia 2020

Abstract: Objective: Studies assessing knowledge about rheumatic fever (RF) and rheumatic heart disease (RHD) are scarce in KSA. The aim of this study was to assess the awareness about ARF and RHD among the population at Taif city, Saudi Arabia. Methods: A cross-sectional study was done on 716 of residents of Taif city. A pre-designed questionnaire that collected data about the participants' demographic characters, their history of sore throat and medication used, participants' k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 22 publications
1
5
1
Order By: Relevance
“…They found that female awareness about sore throat complications, primary prevention, penicillin use and RF primary or secondary prevention ranged from 16.5% to 56%. They further added that the weakest area of awareness was the causes, sore throat management, antibiotic utilisation and the complications of recurrent sore throat [20]. The problem of poor knowledge regarding RHD was also found internationally.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that female awareness about sore throat complications, primary prevention, penicillin use and RF primary or secondary prevention ranged from 16.5% to 56%. They further added that the weakest area of awareness was the causes, sore throat management, antibiotic utilisation and the complications of recurrent sore throat [20]. The problem of poor knowledge regarding RHD was also found internationally.…”
Section: Resultsmentioning
confidence: 99%
“…Another recent Saudi study conducted by Almadhi et al to explore the 2020 who examined the relationship between age and education with each item of the participants' knowledge. They found that participants' age was significantly related to all knowledge items, while education was significantly related to most knowledge items [20]. Concerning the international bias, Nkoke et al found that older age and higher education were significant positive predictors of good knowledge regarding RHD [21].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the required sample size was estimated using Epi Info™ 7.1.5 (Center for Disease Control and Prevention; Atlanta, Georgia, USA) based on the entire population of Makkah city (2,015,000) [16] and the frequency of good understanding of ARF from a previous study (41.6%) [17]. Finally, the minimum required sample size is 373.…”
Section: Sample Size Calculationmentioning
confidence: 99%
“…Knowledge and awareness of the sore throat-ARF-RHD linkage is key to appropriate health-seeking behaviour for the often mild and self-limiting superficial GAS infections. However, globally, there remains a major public knowledge gap for a disease with major societal impact 30–33. A recent systematic review summarised Africa’s enormous community and healthcare worker knowledge gap 34.…”
Section: Key Research Topic 2: Improve Diagnosis and Treatment Of Sup...mentioning
confidence: 99%
“…However, globally, there remains a major public knowledge gap for a disease with major societal impact. [30][31][32][33] A recent systematic review summarised Africa's enormous community and healthcare worker knowledge gap. 34 Additionally, sociocultural factors contribute to the high incidence of ARF/RHD, underscoring the need for engaging families and communities as important stakeholders.…”
Section: Key Research Topic 2: Improve Diagnosis and Treatment Of Sup...mentioning
confidence: 99%